SPIRITUAL EDUCATION AS A STRATEGIC CONTRIBUTION OF HIGHER EDUCATION IN BUILDING FUTURE GLOBAL CIVILIZATION - Syuhud; Farid, Achmad (AL-ADABIYAH: Jurnal Pendidikan Agama Islam, 2025)
Spiritual education serves as a strategic approach for higher education institutions in shaping the future global civilization based on humanistic and divine values. This study aims to analyze the contribution of higher education in embedding spiritual values as the foundation for character formation and peaceful global culture. Using a library research approach, data were gathered from scientific literature on spiritual education, character development, and global civilization building. The results reveal that integrating spiritual education into university curricula enhances students’ spiritual intelligence, moral awareness, and social–ecological responsibility. Spiritual education acts as a transformative instrument in forming holistic individuals who are self-aware and committed to world peace. The findings highlight the strategic role of higher education in fostering a civilized global society through transformative spirituality. Pendidikan spiritual merupakan strategi penting bagi perguruan tinggi dalam membangun peradaban dunia masa depan yang berlandaskan nilai-nilai kemanusiaan dan ketuhanan. Penelitian ini bertujuan untuk menganalisis kontribusi pendidikan tinggi dalam menanamkan nilai spiritual sebagai fondasi pembentukan karakter dan budaya global yang damai. Dengan menggunakan pendekatan studi kepustakaan, data dikumpulkan dari berbagai literatur ilmiah tentang pendidikan spiritual, nilai karakter, dan pembangunan peradaban global. Hasil kajian menunjukkan bahwa integrasi pendidikan spiritual dalam kurikulum perguruan tinggi mampu mengembangkan kecerdasan spiritual mahasiswa, memperkuat moralitas, serta menumbuhkan tanggung jawab sosial dan ekologis. Pendidikan spiritual menjadi instrumen strategis dalam membentuk manusia yang holistik, sadar diri, dan berorientasi pada perdamaian dunia. Temuan ini menegaskan bahwa pendidikan tinggi berperan signifikan dalam mewujudkan peradaban global yang berkeadaban melalui spiritualitas transformatif.